1991
DOI: 10.1007/bf00204184
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau (VHL) disease: distinct phenotypes suggest more than one mutant allele at the VHL locus

Abstract: Summary. As part of an attempt to locate the vonHippel-Lindau locus (VHL) on chromosome 3, we evaluated 41 families with yon Hippel-Lindau disease from the United States and Canada. One large family was identified whose disease phenotype was distinct from typical VHL. The most common disease manifestation was pheochromocytoma occuring in 57% (27/47) of affected family members. Few (4/47) affected family members had symptomatic spinal or cerebellar hemangioblastomas; no affected family member had renal cell car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…8 9 Our present study which includes comprehensive clinical investigation of 125 eligible subjects with the VHL c.505 T/C germline mutation followed by estimation of the overall penetrance by cumulative incidence functions showed that this mutation had an almost complete penetrance (>95% at 75 years). In contrast, the mortality and survival rate is surprisingly comparable to those of the general population of Germany.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…8 9 Our present study which includes comprehensive clinical investigation of 125 eligible subjects with the VHL c.505 T/C germline mutation followed by estimation of the overall penetrance by cumulative incidence functions showed that this mutation had an almost complete penetrance (>95% at 75 years). In contrast, the mortality and survival rate is surprisingly comparable to those of the general population of Germany.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, there are two large families with this mutation in Pennsylvania,5 9 of which at least one originates from the Black Forest. This family was traced to the Schuttertal, a circumscribed area of the Black Forest, and one branch probably migrated from Germany to the USA in the early 1800s 8.…”
mentioning
confidence: 99%
“…Thus, just as Nedd4-1 elevation in a subgroup of hepatocellular carcinomas results in decreased content of Spry2 and a poor outcome (22), it is possible that pVHL elevation in certain hepatocellular carcinomas may result in decreased levels of Spry2 contributing to the growth and progression of these tumors. In von Hippel-Lindau patients, pVHL deficiency leads to development of hemangio- mas and clear cell renal carcinomas (53,54). However, nothing is presently known concerning whether or not pVHL deficiency in these patients alters the levels of Spry isoforms and whether Spry proteins modulate renal clear cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the cloning of the von Hippel-Lindau disease gene, it was suggested that the disease's phenotypic expression might result from allelic heterogeneity. The cloning efforts have identified a number of different types of mutations including deletions, insertions and point mutations [11]. Whether the variety of mutations explains the variable expression of von Hippel-Lindau disease remains to be seen.…”
Section: Discussionmentioning
confidence: 99%